A composite Prussian blue derivative material synthesized by solid-liquid ball milling and its application
Synthesis of composite Prussian blue derivative materials through solid-liquid ball milling method solves the problems of water resource consumption and structural deterioration in traditional processes, improves the conductivity and cyclic stability of the materials, and is suitable for large-scale industrial preparation.
Patent Information
- Application Number
- CN202210574243.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-24
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-05-24
AI Technical Summary
The synthesis process of traditional Prussian blue derivative materials has problems such as large water consumption, long time and structural deterioration, resulting in poor circulation stability of the material.
The composite Prussian blue derivative material is synthesized by solid-liquid ball milling method. By dissolving the salt of transition metal ions in organic or inorganic solvents and ball milling with carbon materials, small particles and stable structures are formed, and the traditional co-precipitation method is avoided. defect.
It improves the conductivity and cyclic stability of the material, enhances the rate performance in aqueous zinc ion batteries, simplifies the synthesis process and is suitable for large-scale industrial preparation.
Smart Images

Figure CN115172679B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical aqueous zinc ion battery materials, and specifically relates to a novel composite Prussian blue derivative material synthesized by solid-liquid ball milling and application thereof. Background Art
[0002] The negative electrode of the aqueous zinc-ion battery uses zinc metal. Its overall reaction principle is to achieve charge transfer through the deintercalation of zinc ions in the positive electrode crystal structure and the deposition and dissolution of zinc negative electrode. The charge and discharge reaction is completed. The difference lies in the different ions embedded in the two. The composition of the aqueous zinc-ion battery mainly includes three parts, namely the positive electrode material, the negative electrode material, and the electrolyte. In addition, there is generally a diaphragm, which is mainly placed between the positive and negative electrodes to avoid direct contact between the positive and negative electrodes and short circuit. The diaphragm in the aqueous zinc-ion battery is generally made of glass fiber or filter paper.
[0003] According to the reaction mechanism of aqueous zinc-ion batteries, the primary requirement for the selection of positive electrode materials is that the charge and discharge potential of the material is within the electrochemical window of the electrolyte to ensure that the battery can be charged and discharged normally and reduce side reactions. In addition, because it is to be used in the field of large-scale energy storage, battery positive electrode materials also need to consider issues such as cost, life, and safety, and also require as high energy density and power density as possible. At this stage, there are relatively few types of zinc ion positive electrode materials studied. The main types of positive electrodes are manganese-based compounds, vanadium-based compounds, Prussian blue compounds, organic electrochemical materials and other types. For example, the research on zinc-manganese batteries in manganese-based compounds has a long history, and also includes other valence states of manganese oxide and zinc manganate. Prussian blue materials are also a type of compound with a large size. Because they have a very stable framework structure, they can achieve rapid deintercalation of zinc ions.
[0004] Prussian blue derivatives (PBAs) have long been considered as potential cathode materials for metal-ion batteries, mainly benefiting from the following structural advantages: (1) The open framework structure with large 3D channels and spacious interstitial spaces allows rapid migration of guest ions with little structural variation. (2) The various combinations of transition metal ions and interstitial alkali metal ion selection in the PBAs lattice make the electrochemical properties of PBAs easy to tailor. (3) The presence of M1 2+ / 3+ and M2 2+ / 3+Two redox active centers, which helps to achieve a higher theoretical specific capacity of PBAs. PBAs have a typical face-centered cubic structure, where Fe(III) bonds with C atoms and M bonds with N atoms, forming FeC6 and MN6 octahedra respectively. Then, these two regular octahedra are connected by (C≡N) bridges to form an open three-dimensional framework. Due to its large interstitial positions and special channels, PBAs allow convenient and reversible electrochemical insertion / extraction of various ions, including zinc ions. The processes of various ions entering and leaving are affected by heteroatoms (such as alkali metal atoms) and water molecules, which are usually present in the interstices of PBAs. PBAs can also be written as A x M[Fe(CN)6]y·zH2O (A = Li, Na, K…). Theoretically, one mole of PBA can achieve two moles of electron transfer because it contains two redox active centers: M 2+ / M 3+ and Fe 2+ / Fe 3+ . However, traditional synthesis processes generally use the multi-component precursor co-precipitation method. This method not only requires a large amount of water resources and time to age the materials, but also easily forms lattice defects and vacancies in Fe(CN)6, blocking the active sites in PBAs, and at the same time causing material structure deterioration and poor cycle stability. Summary of the Invention
[0005] The purpose of the present invention is to overcome the disadvantages and deficiencies existing in the prior art, and to provide a novel solid-liquid ball-milled composite Prussian blue derivative material and its application.
[0006] The technical solution adopted by the present invention is as follows: A novel solid-liquid ball-milled composite Prussian blue derivative material, the chemical general formula of the composite Prussian blue derivative material is A x M1[M2(CN)6] y . nH2O@z carbon material, where 0 < x ≤ 2, 0 < y ≤ 1, 0 ≤ n ≤ 10, 0 ≤ z ≤ 0.1, A = Na or K, and M1 and M2 are transition metal ions;
[0007] Its preparation method includes the following steps:
[0008] (1) Dissolve the salt of transition metal ion M1 in an organic or inorganic solvent to form a homogeneous and stable solution;
[0009] (2) Synthesize A x [M2(CN)6]y.nH2O solid-phase powder and carbon material by ball milling to obtain A x M1[M2(CN)6] y. nH2O@z carbon materials.
[0010] The carbon material is a mixture of one or more of graphite, hard carbon, Ketjen black, Super P, multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, etc.
[0011] In step (1), a salt of the transition metal ion M1 is dissolved in an organic solvent to form a uniform and stable solution. The organic solvent includes ethanol, ethylene glycol, methanol, NMP, etc.
[0012] The organic solvent is ethanol.
[0013] The M1 is one or more of Mn, Fe, Ni, and Co.
[0014] The salt of the transition metal ion M1 is MnSO4 . H2O, MnCl2 . 4H2O, MnBr2 . 4H2O,Mn(CH3COO)2 . 4H2O, Mn(NO3)2.4H2O; FeSO4 . H2O, FeCl2 . 4H2O, FeBr2 . 4H2O,Fe(CH3COO)2 . 4H2O, Fe(NO3)2.4H2O; NiSO4 . H2O, NiCl2 . 4H2O, NiBr2 . 4H2O, Ni(CH3COO)2 . 4H2O, Ni(NO3)2.4H2O; CoSO4 . H2O, CoCl2 . 4H2O, CoBr2 . 4H2O,Co(CH3COO)2 . 4H2O, Co(NO3)2.4H2O or a mixture of one or more thereof.
[0015] The concentration of the salt of the transition metal ion M1 in the organic or inorganic solution containing the salt of the transition metal ion M1 is 0.1-1 mol L -1 .
[0016] A x Fe(CN)6 . The molar ratio of nH2O to the salt of transition metal ion M1 is 1:1.
[0017] The ball milling rate is 200-1000 r / min; and the ball milling time is 1-5 h.
[0018] A positive electrode material, characterized in that the positive electrode material comprises the novel composite Prussian blue derivative material synthesized by solid-liquid ball milling as described above.
[0019] The beneficial effects of the present invention are as follows:
[0020] 1. The present invention uses a solid-liquid ball milling method to synthesize a Prussian blue derivative with smaller particles, thereby avoiding the disadvantages of traditional co-precipitation and hydrothermal methods of synthesizing materials, such as the long time required for synthesizing materials, the need for a large amount of water solvent, and the lattice defects and high interstitial water content introduced during the synthesis process that cause material structure degradation and poor cycle stability. At the same time, the synthesis process of the present invention is simple and efficient, does not require a large amount of water solvent, and can be prepared on a large scale industrially.
[0021] 2. The present invention in-situ coats a layer of carbon material during the material synthesis process, which greatly improves the conductivity of the Prussian blue derivative material and inhibits the structural collapse of the material during the battery charging and discharging process, thereby improving the rate performance and cycle stability of the Prussian blue derivative material in aqueous zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.
[0023] Figure 1 The full battery assembled with the Prussian blue analogue positive electrode material obtained in Example 1 was heated to 0.1 A g -1 The charge and discharge curves at current density of 0.1 A g -1 The current density can reach 129.2 mAh g -1 The discharge capacity of
[0024] Figure 2 The full battery assembled with the Prussian blue analogue composite single-walled carbon nanotube positive electrode material obtained in Example 2 was tested at 0.1 A g -1 The charge and discharge curves under current density of 0.1 A g -1 The current density can reach 169.5 mAh g -1 The discharge capacity of
[0025] Figure 3 The full battery assembled with the Prussian blue analogue positive electrode material obtained in Comparative Example 1 was -1 Charge and discharge curves under current density;
[0026] Figure 4 The infrared spectrum test comparison diagram of the Prussian blue analogue obtained in Example 1, Example 2 and Comparative Example 1 shows that the samples of Example 1 and Example 2 have no peak of interstitial water, indicating that the synthesis method can avoid the generation of interstitial water, while interstitial water exists in Comparative Example 1;
[0027] Figure 5 For Example 1, Example 2, Comparative Example 1 and Comparative Example 2, the temperature range is 0.1-1A g -1 The rate diagrams under the current density of , according to the order of rate performance, are Example 2, Example 1, Comparative Example 2 and Comparative Example 1;
[0028] Figure 6 For Example 3, Example 4 and Comparative Example 3 at 0.1 A g -1 Comparison of charge and discharge curves at current densities of Example 3 at 0.1 A g -1 The current density can reach 157 mAh g -1 The discharge capacity of Example 4 is 0.1 Ag -1 The current density can reach 154.8 mAh g -1 The discharge capacity of Comparative Example 3 is 0.1 A g -1 The current density can reach 127.7 mAh g -1 The discharge capacity of
[0029] Figure 7 For comparative example 4 at 0.1A g -1 The charge and discharge curves at the current density of 0.1A g -1 The specific capacity at a current density of 130.3 mAh g -1 ;
[0030] Figure 8 For comparative example 5 at 0.1A g -1 The charge and discharge curves at the current density of 0.1A g -1 The specific capacity at a current density of 123.8 mAh g -1 . DETAILED DESCRIPTION
[0031] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0032] Embodiment 1:
[0033] The present embodiment provides a method for preparing NaMnHCF, the method comprising the following steps: placing 0.01 mol of Na4Fe(CN)6.10H2O and 20 mL of ethanol solution in which 0.01 mol of Mn(CH3COO)2.4H2O is dissolved in a stainless steel ball mill, the ball milling rate is 500 r / min, the ball milling is performed for 4 h, after the ball milling is completed, the ball mill is transferred to a 120 °C vacuum drying oven for drying for 7 h; then the mixture is ground in an agate mortar, and transferred to 100 mL of ethanol for soaking for 8 h. After the soaking is completed, the precipitate is centrifuged and washed 3 times with deionized water and ethanol respectively. The centrifuged precipitate is collected and placed in a vacuum drying oven at 120 °C for drying for 8 h to obtain the NaMnHCF.
[0034] The synthesized NaMnHCF material was made into a battery electrode, zinc foil was used as the battery negative electrode, the electrolyte was an aqueous zinc ion battery electrolyte, and a glass fiber membrane was used as a battery separator to assemble a full battery, and the electrochemical performance of the full battery was tested.
[0035] Figure 1 The full battery assembled with the Prussian blue analogue positive electrode material obtained in Example 1 was heated to 0.1 A g -1 Charge and discharge curves at different current densities.
[0036] Embodiment 2:
[0037] This embodiment provides a method for preparing NaMnHCF@single-walled carbon nanotubes, the preparation method comprising the following steps:
[0038] 0.01 mol of Na4Fe(CN)6.10H2O was placed in a vacuum drying oven at 80 °C for 12 h to remove crystal water, and then 0.01 mol of Mn(CH3COO)2.4H2O was dissolved in 20 mL of ethanol to form a transparent solution. 30.4 mg of single-walled carbon nanotubes were weighed into the above solution and ultrasonicated with a cell disruptor for 20 min. The above powder and ultrasonicated solution were placed in a stainless steel ball mill at a ball milling rate of 1000 r / min for 5 h. After the ball milling, the ball mill was transferred to a 120 °C vacuum drying oven for drying for 7 h; then ground in an agate mortar and transferred to 100 mL of ethanol for soaking for 8 h. After soaking, the precipitate was centrifuged and washed 3 times with deionized water and ethanol respectively. The centrifugal precipitate was collected and placed in a vacuum drying oven at 120 °C for 8 h to obtain the NaMnHCF@single-walled carbon nanotubes.
[0039] The synthesized NaMnHCF@single-walled carbon nanotube material was made into a battery electrode, zinc foil was used as the battery negative electrode, the electrolyte was an aqueous zinc ion battery electrolyte, and a glass fiber membrane was used as a battery separator to assemble a full battery, and the electrochemical performance of the full battery was tested.
[0040] Figure 2 The full battery assembled with the Prussian blue analogue composite single-walled carbon nanotube positive electrode material obtained in Example 2 was tested at 0.1 A g -1 Charge and discharge curves at different current densities.
[0041] Embodiment 3:
[0042] This embodiment provides a method for preparing KMnHCF, the preparation method comprising the following steps:
[0043] 0.01 mol of K3Fe(CN)6 and 20 mL of ethanol solution containing 0.01 mol of Mn(CH3COO)2.4H2O were placed in a stainless steel ball mill at a ball milling rate of 500 r / min for 3.5 h. After the ball milling, the ball mill was transferred to a 120°C vacuum drying oven for drying for 7 h; then ground in an agate mortar and transferred to 100 mL of ethanol for soaking for 8 h. After soaking, the precipitate was centrifuged and washed 3 times with deionized water and ethanol respectively. The centrifuged precipitate was collected and placed in a vacuum drying oven at 120°C for drying for 8 h to obtain the KMnHCF.
[0044] The above-synthesized KMnHCF material was made into a battery electrode, a zinc foil was used as the battery negative electrode, the electrolyte was an aqueous zinc ion battery electrolyte, and a glass fiber membrane was used as a battery separator to assemble a full battery, and the electrochemical performance of the full battery was tested.
[0045] Embodiment 4:
[0046] This embodiment provides a method for preparing KMnHCF@single-walled carbon nanotubes, the preparation method comprising the following steps:
[0047] Weigh 0.01 mol of K3Fe(CN)6, then dissolve 0.01 mol of Mn(CH3COO)2.4H2O in 20 mL of ethanol to form a transparent solution, weigh 30.4 mg of single-walled carbon nanotubes in the above solution and use a cell disruptor to ultrasonicate for 20 minutes, place the above powder and ultrasonicate solution in a stainless steel ball mill, the ball milling rate is 1000 r / min, ball milling for 5 hours, after ball milling, transfer the ball mill to a 120 ℃ vacuum drying oven and dry for 7 hours; then grind it in an agate mortar and transfer it to 100 mL of ethanol and soak it for 8 hours. After soaking, the precipitate is centrifuged and washed 3 times with deionized water and ethanol respectively. Collect the centrifugal precipitate and place it in a vacuum drying oven at 120 ℃ and dry it for 8 hours to obtain the NaMnHCF@single-walled carbon nanotubes.
[0048] The above-synthesized KMnHCF@single-walled carbon nanotube material was made into a battery electrode, zinc foil was used as the battery negative electrode, the electrolyte was an aqueous zinc ion battery electrolyte, and a glass fiber membrane was used as a battery separator to assemble a full battery, and the electrochemical performance of the full battery was tested.
[0049] Comparative Example 1:
[0050] 0.01 mol of Na4Fe(CN)6.10H2O and 3 g of polyvinyl pyrrolidone were dissolved in 150 mL of deionized water as solution A, and 0.01 mol of Mn(CH3COO)2.4H2O and 15 g of NaCl were dissolved in 100 mL of deionized water as solution B. Solution B was pumped into solution A at a rate of 0.5 mL / min using a peristaltic pump while stirring solution A at a rate of 200 r / min. After all solution B was pumped into solution A, stirring was stopped and the solution was placed in a 60 ℃ oven for aging for 24 h.
[0051] The Prussian blue derivative material prepared in Comparative Example 1 was used as the positive electrode, zinc metal as the negative electrode, and a glass fiber membrane as a battery separator to form a button battery.
[0052] Figure 5 The full battery assembled with the Prussian blue analogue positive electrode material obtained in Comparative Example 1 was 0.1-2 A g -1 Charge and discharge curves under current density.
[0053] Figure 6 This is a comparison chart of infrared spectrum tests of the Prussian blue analogues obtained in Example 1, Example 2 and Comparative Example 1.
[0054] Comparative Example 2:
[0055] 0.01 mol of Na4Fe(CN)6.10H2O and 0.01 mol of Mn(CH3COO)2.4H2O were placed in a stainless steel ball mill at a ball milling rate of 500 r / min for 3.5 h. After the ball milling was completed, the ball mill was transferred to a 120 °C vacuum drying oven for drying for 7 h; then ground in an agate mortar and transferred to 100 mL of ethanol for soaking for 8 h. After soaking, the precipitate was centrifuged and washed three times with deionized water and ethanol respectively. The centrifugal precipitate was collected and placed in a vacuum drying oven at 120 °C for 8 h to obtain the NaMnHCF.
[0056] The Prussian blue derivative material prepared in Comparative Example 2 was used as the positive electrode, zinc metal as the negative electrode, and a glass fiber membrane as a battery separator to form a button battery.
[0057] Figure 1 For Example 1, Example 2, Comparative Example 1 and Comparative Example 2, the temperature range is 0.1-1A g -1Comparison of rate diagrams at current density.
[0058] Comparative Example 3:
[0059] 0.01 mol of K3Fe(CN)6 and 0.01 mol of Mn(CH3COO)2.4H2O were placed in a stainless steel ball mill at a ball milling rate of 500 r / min for 3.5 h. After the ball milling was completed, the ball mill was transferred to a 120°C vacuum drying oven for drying for 7 h; then ground in an agate mortar and transferred to 100 mL of ethanol for soaking for 8 h. After soaking, the precipitate was centrifuged and washed three times with deionized water and ethanol respectively. The centrifugal precipitate was collected and placed in a vacuum drying oven at 120°C for drying for 8 h to obtain the KMnHCF.
[0060] The Prussian blue derivative material prepared in Comparative Example 3 was used as the positive electrode, zinc metal as the negative electrode, and a glass fiber membrane as a battery separator to form a button battery.
[0061] Figure 6 For Example 3, Example 4 and Comparative Example 3 at 0.1A g -1 Comparison of charge and discharge curves under different current densities.
[0062] Comparative Example 4:
[0063] Weigh 0.01 mol of Na4Fe(CN)6, then dissolve 0.01 mol of Mn(CH3COO)2.4H2O in 20 mL of ethylene glycol to form a transparent solution. The ball milling rate is 1000 r / min, and the ball milling is performed for 5 h. After the ball milling is completed, the ball milling jar is transferred to a 120 ℃ vacuum drying oven and dried for 7 h; then it is ground in an agate mortar and transferred to 100 mL of ethanol and soaked for 8 h. After the soaking is completed, the precipitate is washed by centrifugation with deionized water and ethanol three times each. Collect the centrifugal precipitate and place it in a vacuum drying oven at 120 ℃ and dry it for 8 h.
[0064] The synthesized NaMnHCF material was made into a battery electrode, zinc foil was used as the battery negative electrode, the electrolyte was an aqueous zinc ion battery electrolyte, and a glass fiber membrane was used as a battery separator to assemble a full battery, and the electrochemical performance of the full battery was tested.
[0065] Figure 7 For comparative example 4 at 0.1A g -1 Charge and discharge curves at current density.
[0066] Comparative Example 5:
[0067] Weigh 0.01 mol of Na4Fe(CN)6, then dissolve 0.01 mol of Mn(CH3COO)2.4H2O in 20 mL of water to form a transparent solution. The ball milling rate is 1000 r / min, and the ball milling is performed for 5 h. After the ball milling is completed, the ball milling jar is transferred to a 120 ℃ vacuum drying oven and dried for 7 h; then it is ground in an agate mortar and transferred to 100 mL of ethanol and soaked for 8 h. After the soaking is completed, the precipitate is washed by centrifugation with deionized water and ethanol three times each. The centrifugal precipitate is collected and placed in a vacuum drying oven at 120 ℃ for 8 h.
[0068] The synthesized NaMnHCF material was made into a battery electrode, zinc foil was used as the battery negative electrode, the electrolyte was an aqueous zinc ion battery electrolyte, and a glass fiber membrane was used as a battery separator to assemble a full battery, and the electrochemical performance of the full battery was tested.
[0069] Figure 8 For comparative example 5 at 0.1A g -1 Charge and discharge curves at current density.
[0070] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A composite Prussian blue derivative material synthesized by solid-liquid ball milling, characterized in that: The chemical general formula of the composite Prussian blue derivative material is A x M1[M2(CN)6] y. nH2O@z carbon material, where 0 < x ≤ 2, 0 < y ≤ 1, 0 ≤ n ≤ 10, 0 ≤ z ≤ 0.1, A = Na or K, and M1 and M2 are transition metal ions; The preparation method comprises the following steps: (1) dissolving a salt of a transition metal ion M1 in an organic or inorganic solvent to form a uniform and stable solution; (2) an organic or inorganic solution containing a salt of transition metal ion M1, A x [M2(CN)6]y.nH2O solid phase powder and carbon material were synthesized by ball milling x M1[M2(CN)6] y. nH2O@z carbon materials; The concentration of the salt of the transition metal ion M1 in the organic or inorganic solution containing the salt of the transition metal ion M1 is 0.1-1 mol L -1 ; The A x [M2(CN)6]y.nH2O solid phase powder is A x Fe(CN) 6. nH2O,A x Fe(CN) 6. The molar ratio of nH2O to the salt of transition metal ion M1 is 1:1; The ball milling rate is 200-1000 r / min; the ball milling time is 1-5 h.
2. The composite Prussian blue derivative material synthesized by solid-liquid ball milling according to claim 1, characterized in that: The carbon material is a mixture of one or more of graphite, hard carbon, Ketjen black, Super P, multi-walled carbon nanotubes, single-walled carbon nanotubes, and graphene.
3. The composite Prussian blue derivative material synthesized by solid-liquid ball milling according to claim 1, characterized in that: In step (1), a salt of transition metal ion M1 is dissolved in ethanol to form a uniform and stable solution.
4. The composite Prussian blue derivative material synthesized by solid-liquid ball milling according to claim 1, characterized in that: The M1 is one or more of Mn, Fe, Ni, and Co.
5. The composite Prussian blue derivative material synthesized by solid-liquid ball milling according to claim 4, characterized in that: The salt of the transition metal ion M1 is a mixture of one or more of MnSO4.H2O, MnCl2.4H2O, MnBr2.4H2O, Mn(CH3COO)2.4H2O, Mn(NO3)2.4H2O; FeSO4.H2O, FeCl2.4H2O, FeBr2.4H2O, Fe(CH3COO)2.4H2O, Fe(NO3)2.4H2O; NiSO4.H2O, NiCl2.4H2O, NiBr2.4H2O, Ni(CH3COO)2.4H2O, Ni(NO3)2.4H2O; CoSO4.H2O, CoCl2.4H2O, CoBr2.4H2O, Co(CH3COO)2.4H2O, Co(NO3)2.4H2O.
6. A positive electrode material, characterized in that The positive electrode material comprises the composite Prussian blue derivative material synthesized by solid-liquid ball milling as described in any one of claims 1 to 5.
Citation Information
Patent Citations
Preparation method of prussian blue material
CN109775726A
Prussian blue sodium ion battery positive electrode material and preparation method thereof
CN113488646A